Development of IS teaching in North-America: An analysis of model curricula - Carola Schauer; Tobias Schmeing (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2007)
This research report is part of a series of papers on the development and status of the Information Systems (IS) discipline in North-America and Wirtschaftsinformatik (WI) its counterpart in the German speaking countries (Germany, Austria, Switzerland). The corresponding research project (IFWIS) aims at comparing both disciplines. It is funded by the German Research Foundation (DFG). In this report we aim at reconstructing the development of teaching programs in IS at North-American universities. To this end official model curricula for undergraduate and graduate IS programs since the 1970s until today serve as primary source for relevant prescriptive as well as descriptive information. Our analysis results indicate that the IS discipline has undergone considerable changes in terms of (recommended) teaching contents and structures, the role of practice experience in teaching, and the variety of recommended future job positions. An additional literature analysis focuses on the actual adoption of model curricula at US universities. Analysis results indicate that IS programs are rather diverse and have very few courses in common - even when focusing on IS core courses.
Keywords: 650; Informationssystem; Wirtschaftsinformatik; Studium; USA